Effect of feeding type and artisanal process in microstructural and physicochemical parameters of fresh and ripened goat cheese - Ramírez-Rivera, Emmanuel J.; Herrera Corredor, José Andrés; Toledo López, Víctor Manuel; Sauri-Duch, Enrique; Rodríguez-Miranda, Jesús; Juárez Barrientos, José Manuel; Díaz-Rivera, Pablo; Herman-Lara, Erasmo (International Food Research Journal, 2021)
The objective of the present work was to determine the influence of feeding type and artisanal process on microstructural and physicochemical parameters of goat cheeses. The cheeses were made with goat's milk from goats which were fed with different forages: (1) reed (Cissu verticillata) and King grass (Saccharum sinense), (2) mulberry (Morus alba) leaves and orange (Citrus sinensis) peels, (3) alfalfa (Medicago sativa) and corn (Zea mays) stover, and (4) bellota (Quercus ilex) and Kikuyu grass (Pennisetum clandestinum). Fresh and ripened artisanal cheeses were analysed by scanning electron microscopy and image analysis. Results showed that goat’s milk of goats fed with mulberry leaves and orange peels generated larger conglomerates of fat in both types of cheeses, while the microstructure of the rest of the cheeses presented protein networks. A low pH and moisture content contributed to the formation of lactose crystals which ended in a compact microstructure, propitiating, reduction of the number of pores, porosity, and increase in the breakability of ripened cheeses. Pores of elongated shapes with irregular edges characterised the microstructure of both kinds of cheeses. Through discriminant analysis, it was found that the effect of the type of cheese and type of goat feeding influenced the microstructural and physicochemical parameters such as pore number, porosity, pore size, pore perimeter, roundness, FF, AR, SOL, tortuosity, INP-DI, PAZ, fat, moisture, and pH.
Keywords: Análisis de imágenes; Distribución del tamaño de los poros; Porosidad; Microscopio electrónico de barrido